2020
DOI: 10.1007/s13272-020-00447-w
|View full text |Cite
|
Sign up to set email alerts
|

The acceptance of civil drones in Germany

Abstract: In recent years, civil drones have become more and more visible in everyday life. There are numerous reports in the media covering a variety of drone aspects and technical developments. In addition, everyone is used to bird's-eye views as common features in television, movies and photography. However, little is known about how the public perceives this development. This article reports the results of a representative national study on the acceptance of civilian drones. Overall, a balanced but slightly positive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
62
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 65 publications
(81 citation statements)
references
References 8 publications
8
62
3
Order By: Relevance
“…Currently, the usage of air taxis has only garnered limited acceptance among the public. In a representative study conducted in Germany in 2018 [15], 86% of the respondents in a telephone survey indicated they would not use air taxis. Moreover, even being positive about using UAM does not necessarily mean to accept it flying above the own dwelling: among the 14% of respondents who agreed either fully (4.9%) or slightly (9.2%) with the prospect of using unmanned air taxis, only two out of three would accept air taxis flying above their home during daytime, and less than half would agree to night-time flyovers [16].…”
Section: Uam Acceptancementioning
confidence: 99%
See 1 more Smart Citation
“…Currently, the usage of air taxis has only garnered limited acceptance among the public. In a representative study conducted in Germany in 2018 [15], 86% of the respondents in a telephone survey indicated they would not use air taxis. Moreover, even being positive about using UAM does not necessarily mean to accept it flying above the own dwelling: among the 14% of respondents who agreed either fully (4.9%) or slightly (9.2%) with the prospect of using unmanned air taxis, only two out of three would accept air taxis flying above their home during daytime, and less than half would agree to night-time flyovers [16].…”
Section: Uam Acceptancementioning
confidence: 99%
“…Concerns connected with mishaps all raised concerns in the range of 72% to 75%, followed closely by concerns about animal welfare. Concerns about noise were confirmed less frequently (53%) [15]. However, among all concerns, those relating to noise are the strongest predictor of acceptance of civil drones: people who are concerned about noise show least acceptance [19].…”
Section: Uam Acceptancementioning
confidence: 99%
“…Furthermore the usage of air taxis finds only little acceptance among the public. In a representative study in Germany, 85% of the respondents in a telephone survey indicated they would not use air taxis [7]. Even among those who would consider using UAM, their acceptance is likely to vanish when air taxis are flying above their house or workplace.…”
Section: Noise Concernsmentioning
confidence: 99%
“…However, to establish drone noise standards and legislations to address and minimize noise issues, among others, a profound knowledge of acoustical characteristics depending on operational procedures as well as related health impacts on the population is necessary. Limiting the noise impact on the population at an early stage is crucial, even more so because the opinion of the population on drones still seems to be forming [ 4 ]. Thus, the acceptance might develop rather advantageously or disadvantageously for drones, depending on the perceived relative importance of benefits or (noise) risks by drones [ 1 , 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Limiting the noise impact on the population at an early stage is crucial, even more so because the opinion of the population on drones still seems to be forming [ 4 ]. Thus, the acceptance might develop rather advantageously or disadvantageously for drones, depending on the perceived relative importance of benefits or (noise) risks by drones [ 1 , 4 ].…”
Section: Introductionmentioning
confidence: 99%